Ending Neonatal Deaths From Hypothermia in Sub-Saharan Africa: Call for Essential Technologies Tailored to the Context - Brambilla Pisoni, Giorgia; Gaulis, Christine; Suter, Silvan; Rochat, Michel A.; Makohliso, Solomzi; Roth-Kleiner, Matthias; Kyokan, Michiko; Pfister, Riccardo E.; Schönenberger, Klaus (Frontiers in Public Health, 2022)
Neonatal death represents a major burden in Sub-Saharan Africa (SSA), where the main conditions triggering mortality, such as prematurity, labour complications, infections, and respiratory distress syndrome, are frequently worsened by hypothermia, which dramatically scales up the risk of death. In SSA, the lack of awareness on the procedures to prevent hypothermia and the shortage of essential infant devices to treat it are hampering the reduction of neonatal deaths associated to hypothermia. Here, we offer a snapshot on the current available medical solutions to prevent and treat hypothermia in SSA, with a focus on Kenya. We aim to provide a picture that underlines the essential need for infant incubators in SSA. Specifically, given the inappropriateness of the incubators currently on the market, we point out the need for reinterpretation of research in the field, calling for technology-based solutions tailored to the SSA context, the need, and the end-user.